Outcome of pregnancy in patients with congenital heart diseases. - Akhter, N; Rahman, F; Salman, M; Anam, K; Banerjee, SK; Amin, SA; Jahan, S; Hasen, Z; Rahman, MM; Uddin, MJ; Rashid, MA; Hafiz, MG; et al. (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):620-4 The abstract of this article is available on the PubMed website